Generalised versus Regional Odontodysplasia: Diagnosis, Transitional Management, and Long-Term Followup—A Report of 2 Cases - Mostafa Ibrahim Mostafa; Nehad Samir Taha; Mennat Allah Ismail Mehrez (Case Reports in Dentistry)
Background. Odontodysplasia is an uncommon condition. It can be localised or generalised, isolated or part of a syndrome. Case Report. We first report the case of an 8.5-year-old boy who presented with abnormally shaped teeth and multiple intraoral abscesses. Findings of clinical and radiographic examinations were consistent with those of generalised odontodysplasia. A 2-step, conservative treatment plan was executed with a 10-year followup. Step 1 was root canal treatment of nonvital teeth. Step 2 was crowning without preparation of new vital, erupted, and malformed teeth. The second case is that of a 12-year-old girl who presented with lack of teeth in the upper-left quadrant. The impacted teeth were exposed surgically, and fixed restoration was performed for temporary aesthetic improvement. Conclusion. Instead of tooth extraction, an approach previously used in similar cases, conservative management is feasible and offers better prosthetic treatment options for the future.